The Influence of Internal Marketing on Job Satisfaction with Employee Engagement as a Mediator (Survei of Bank Syariah Indonesia Employees in Ternate) - Haji, Sulfi Abdul; Imam, Muhammad Thahrim; Ridwan, Ika Wulandari (ITB AAS INDONESIA Surakarta, 2023)
The abstract is written in English. It should contain the primary issues of study, the Understanding the elements influencing employee performance is critical since it can determine organizational success. In other words, whether or not employees perform well will significantly impact the organization's future production and profitability. This study aims to see how internal marketing affects Job satisfaction by using employee engagement as a moderating variable. Employees of Bank Syariah Indonesia in Ternate are the research subjects. This study is quantitative. Validity and reliability tests should be performed on the research instrument. Descriptive statistical analysis, SEM (Structural Equation Model), and PLS (Partial et al.) analysis were used to analyze the data. According to the study's findings, internal marketing has no positive or substantial effect on job satisfaction. Internal marketing has a significant and beneficial impact on employee engagement. Employee involvement has a significant and positive impact on job satisfaction. Employee engagement serves as a bridge between internal marketing and Job satisfaction.